1979
DOI: 10.3109/15563657908989894
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxyamphetamine Overdose

Abstract: MDA was indicated in the death of a 35-year-old male. Blood, tissue, and urine concentrations of MDA were measured by ultraviolet spectrophotometry after identification by gas chromatography/mass spectrometry. The concentrations found were within the range of previously reported fatal MDA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Methylenedioxyamphetamine (MDA) was firstly reported as the main metabolite of MDMA in one case after the ingestion of a single dose [4]. Many fatal cases have been published giving both MDMA and MDA concentrations [5][6][7][8][9]. 4-Hydroxy-3-methoxymethamphetamine (HMMA) and other metabolites were reported first in rats [10] and then in human urine in one post-mortem case [11].…”
Section: Introductionmentioning
confidence: 95%
“…Methylenedioxyamphetamine (MDA) was firstly reported as the main metabolite of MDMA in one case after the ingestion of a single dose [4]. Many fatal cases have been published giving both MDMA and MDA concentrations [5][6][7][8][9]. 4-Hydroxy-3-methoxymethamphetamine (HMMA) and other metabolites were reported first in rats [10] and then in human urine in one post-mortem case [11].…”
Section: Introductionmentioning
confidence: 95%
“…These data show that high MDMA concentrations can be found in organs such as the brain (i.e. [15,44,[96][97][98][99][100][101][102][103][104] ), which indicated that concentrations in cardiac blood are obviously higher than those in peripheral blood. The latter confirms that post-mortem redistribution due to diffusion from higher to lower concentration can easily take place, mainly at longer post-mortem intervals and when putrefaction occurs.…”
Section: Thanato-toxicological Datamentioning
confidence: 79%
“…Plurivascular stasis with intravascular coagulation and massive edema of the lungs are succinctly described only in older reports of cases of MDA intoxication [18][19][20][21][22], and only Dowling et al [10], and recently Forrest et al [23], give macroscopic descriptions based on a substantial case series. hyperthermia and disseminated intravascular coagulation (DIC), but the macro-and microscopic findings have not yet been classified or defined in a satisfactory manner.…”
Section: Discussionmentioning
confidence: 99%